Peningkatan Kompetensi Literasi Digital Guru Melalui Bimtek Pembuatan Media Pembelajaran Menggunakan Magic School - Ayu Ningrum, Tia; Anisah; Rifma; Sulastri (Universitas Negeri Surabaya, 2024)
Kamang Magek is one of the sub-districts that is an expansion of the Tilatang Kamang sub-district in Agam Regency. The current problem is the low competence of teachers, namely 54.77% and there are still many teachers who do not understand digital technology, namely 97.5% of teachers. This means that there are still many teachers who have not been able to carry out learning using technology and create learning media using digital media. For this reason, it is necessary to improve teacher competence, namely by conducting technical guidance on making learning media using digital technology for elementary school teachers using AI Magic School. The method in this activity is by establishing partner cooperation, setting the activity time, sharing best practices, teacher competency training and technical guidance on making learning media. Based on the results of the pretest and posttest in the form of a questionnaire, it is known that the teacher's literacy competence before training was 73% and increased to 97% after training. Then for the ability to use magic school there was also an increase where before the training the value of the teacher's ability to use magic school was 68 while after the training the value of the teacher's ability to use magic school became 98%. This means that training can increase teachers' digital competence and understanding of using AI Magic School.